Secretory units of islets in transplantation index is a useful predictor of insulin requirement in Japanese type 2 diabetic patients. Issue 5 (26th December 2013) - Iwata, Minoru; Matsushita, Yumi; Fukuda, Kazuhito; Wakura, Tatsurou; Okabe, Keisuke; Koshimizu, Yukiko; Fukushima, Yasuo; Kobashi, Chikaaki; Yamazaki, Yu; Honoki, Hisae; Suzuki, Hikari; Kigawa, Mika; et al.
Abstract Aims/Introduction The objective of the present study was to clarify the validity of β‐cell function‐related parameters for predicting the insulin requirement of Japanese type 2 diabetic patients. Materials and Methods In 188 patients with type 2 diabetes who had been admitted to the University of Toyama Hospital (Toyama, Japan) without receiving insulin therapy, we carried out a cross‐sectional study examining the relationship between the homeostasis model assessment of β‐cell function (HOMA‐β) and C‐peptide‐based indices, and also carried out a retrospective study to examine the utility for predicting insulin requirement of several β ‐cell function‐related indices using a receiver operating characteristic (ROC) curve analysis. Results The secretory units of islets in transplantation index (SUIT) had the strongest correlation with HOMA‐β, followed by the fasting serum C‐peptide immunoreactivity index (CPI); the fasting serum C‐peptide immunoreactivity itself (F‐CPR) had the least correlation. The CPI, HOMA‐β and SUIT were significantly lower in the insulin‐requiring group than in the non‐insulin‐requiring group, even after adjustments for confounding factors (P < 0.01). The areas under the ROC curve for insulin requirement were 0.622, 0.774, 0.808, and 0.759 for F‐CPR, CPI, SUIT, and HOMA‐β, respectively. The cut‐off values of SUIT, CPI, and HOMA‐β for an over 80% specificity for the prediction of insulin therapy were 23.5, 1.00, and 14.9, respectively. Conclusions The present study shows that SUIT is the best predictor of insulin requirement among these β‐cell function‐related markers.